A critical appraisal of the international factors in "One Country, Two Systems" and democratization in Hong Kong. Issue 2 (8th February 2019) - Chan, Kenneth Ka Lok; Chong, King Man Eric
Abstract : Purpose: The purpose of this paper is to present an analytical framework to examine the impact of international factors on "One Country, Two Systems" in general and Hong Kong's democratization in particular. Design/methodology/approach: The paper has adopted a behavioral approach to identify the agents, mechanisms and observable facets of external–internal interactions. Findings: The need for international recognition on the performance of the Hong Kong Special Administrative Region (HKSAR) under Chinese sovereignty has provided external actors with the necessary leverage. Though the impact of the international community has been indirect and limited, the authors have identified two mechanisms – lesson drawing and socialization – whereby the impact of international actors and their actions towards Hong Kong may be subtly felt. Moreover, there are at least three observable facets of external actions which are pertinent to the democracy issue. At the end of day, the external impacts will be determined not by the international actors per se but the balance of power between the domestic actors in Hong Kong. Originality/value: There is a scholarly consensus that international factors matter to Hong Kong. But there has been a lack of serious investigation as to why and how they matter. The observable facets of external–internal interactions and the mechanisms identified in this work have not only enriched our understanding of the relevance of external factors in Hong Kong affairs, but also provided a sound foundation for future research.